2018
DOI: 10.1093/carcin/bgy008
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3zeta is involved in the anticancer effect of metformin in colorectal carcinoma

Abstract: Metformin is a promising drug for cancer prevention and treatment, especially in the diabetic population. We aimed to test whether 14-3-3zeta affects the anticancer effect of metformin on colorectal carcinoma (CRC). In this study, we confirmed that higher 14-3-3zeta expression was found in CRC tissues than in pericarcinoma tissues, and in CRC tissue of patients with diabetes than in those without diabetes. A knockdown of 14-3-3zeta inhibited CRC proliferation and promoted apoptosis in vitro and in vivo. Then, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Elevated expression of 14-3-3 δ protein have been reported recently in head and neck squamous cell carcinomas [ 10 ], liver cancer [ 11 ], nonsmall cell lung cancer, colorectal carcinoma [ 12 ], and breast cancer [ 13 ]. In our previous study, we also found the level of 14-3-3 δ protein is elevated in cholangiocarcinoma, but the samples contained a large portion of intrahepatic CCA [ 14 ], the role and expression of 14-3-3 δ in the development of extrahepatic CCA has not been well studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated expression of 14-3-3 δ protein have been reported recently in head and neck squamous cell carcinomas [ 10 ], liver cancer [ 11 ], nonsmall cell lung cancer, colorectal carcinoma [ 12 ], and breast cancer [ 13 ]. In our previous study, we also found the level of 14-3-3 δ protein is elevated in cholangiocarcinoma, but the samples contained a large portion of intrahepatic CCA [ 14 ], the role and expression of 14-3-3 δ in the development of extrahepatic CCA has not been well studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of 14-3-3ζ and its related isoforms in the context of cancer has long been associated with poor clinical outcomes due to increased cell survival [15, 42] . Although it has been demonstrated that inhibiting 14-3-3ζ triggers apoptosis in cancer cells, there are currently no approved chemotherapies that target 14-3-3ζ:BAD interactions [17] . The primary aim of this study was to explore the possibility of identifying anti-CRC compounds by their capacity to interrupt 14-3-3ζ:BAD interactions, and this was executed by the generation of a biosensor capable of detecting 14-3-3ζ:BAD PPIs.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in 14-3-3 protein expression, especially the 14-3-3ζ isoform, have been observed in a variety of cancers, such as those of colon, breast, lung, and pancreas [15] , and overexpression of 14-3-3ζ may mediate tumor resistance to chemotherapy due to its anti-apoptotic functions [16] . Depletion of 14-3-3ζ has been found to induce the apoptosis of CRC cells in vitro and in vivo [17] , and suggesting that identifying or developing novel disruptors of 14-3-3 protein:BAD protein-protein interactions (PPIs) might represent a promising approach towards the treatment of various cancers, including CRC. Drug development involving de novo synthesis and validation of novel chemical entitites is an incredibly expensive and time-consuming endeavor that typically yields a low success rate [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the AMPK-dependent effect of metformin has been implied to be beneficial for many other pathogeneses, such as cancer [70]. For the critical role of cancer stem/initiating cells in tumorigenesis and cancer development, researchers explored whether metformin affects cancer initiating cells, and found that metformin (1 mM) activates hexaribonucleotide-binding protein 3(FOX3) via AMPK activation, which is sufficient to promote the differentiation of glioma-initiating cells into nontumorigenic cells [71].…”
Section: Metfromin Exerts Its Effect In An Ampk-dependent Mannermentioning
confidence: 99%